Electrocardiographic findings for predicting the left anterior descending artery chronic total occlusion in patients with inferior ST-segment elevation myocardial infarction - Xiaobin Zheng; Zhaofu Zhang; Bingqi Yao; Haiyan Wu (Scientific Reports)
Abstract In determining the culprit vessel responsible for inferior ST-segment elevation myocardial infarction (STEMI) as either the right coronary artery (RCA) or left circumflex (LCX), the electrocardiographic value has been validated. However, its ability to predict whether inferior STEMI is complicated by left anterior descending artery (LAD) chronic total occlusion remains uncertain. Based on the involvement of arteries other than the culprit vessels, 189 patients with inferior STEMI from our chest pain center were categorized into four groups: LAD occlusion group (n = 20), LAD stenosis > 50% group (n = 116), normal LAD group (n = 27), and other vessel stenosis > 50% group (n = 26). All groups underwent coronary angiography within 24 h of admission, and electrocardiogram (ECG) and clinical data were retrospectively analyzed. In the LAD occlusion group, hypertension was significantly more prevalent (P = 0.015). Although there was a trend toward higher previous cerebral infarction and lower diabetes prevalence in the Normal LAD group, neither was statistically significant (P = 0.070 and P = 0.088). The LAD occlusion group demonstrated the highest serum N-terminal pro-B-type natriuretic peptide (NT-proBNP) levels and the most reduced LVEF, with a higher susceptibility to cardiogenic shock (P < 0.01). This group also had a higher use of intra-aortic balloon pump (IABP) and a greater occurrence of ventricular fibrillation or tachycardia compared to the other groups (P < 0.05). The QRS duration in lead V4 (QRS V4) was 99.4 ± 19.1 ms in the LAD occlusion group, 87.5 ± 14.9 ms in the LAD stenosis group, 89.6 ± 11.4 ms in the normal LAD group, and 87.7 ± 11.7 ms in the other vessel stenosis group (P = 0.010). The difference between ST-segment depression in V4 and ST-segment elevation in lead III (ST V4↓- ST III↑) in the LAD occlusion group was the largest at -0.06 (-1.19, 1.05) mm (P = 0.029). ROC curve analysis revealed that the sensitivity of QRS V4 > 97.7ms and ST V4↓- ST III↑> 0 mm diagnosing inferior STEMI complicated with LAD occlusion was 54.5% and 50%, with a specificity of 75.1% and 78.0%, respectively. Multivariate logistic regression analysis indicated that QRS V4 (OR = 1.062, P = 0.003), ST V4↓- ST III↑ (OR = 1.641, P = 0.050), and Killip classification (OR = 2.115, P = 0.004) were all independent risk factors for LAD occlusion. In patients with inferior STEMI complicated by LAD occlusion without anterior myocardial infarction, cardiac function is poorer. The ST-segment deviation between the leads V4 and III, and the duration of QRS in the lead V4, can aid in diagnosis.